Concurso de crimes, de normas, e a autolavagem no direito penal brasileiro - João Carlos Gonçalves Krakauer Maia (2019)
This study focuses on the subjects of formal and material joinder of offenses in Brazilian Criminal Law, with special attention to how they manifest in money laundering. Accepting self-laundering, that is, admitting that the perpetrator of a predicate offense may additionally be punished for money laundering requires analyzing a series of criminal elements and institutions, lest the prohibition of bis in idem be violated. In order to do so, it is necessary, at first, to examine the principles governing joinder of offenses: the principle of full appraisal of the conduct and of prohibition of bis in idem. It is also necessary to debate unity or plurality of conducts, as well as other kinds of formal and material joinder of offenses admitted in Brazilian Criminal Law. Moreover, it demands analyzing the main characters of money laundering, with special attention to the legal interest protected by this criminal institution, as well as discussing when multiple conducts defined as money-laundering crimes represent a single delict or multiple ones. With that established, it will be possible to assess the conditions that characterize self-laundering and, then, study some cases of joinder of laundering and the predicate offense.